Intestinal protozoa infections and associated factors among diarrheal under-five children in Borena district, central Ethiopia - Alebie Mesfin; Woynshet Gelaye; Getaneh Alemu (Parasite Epidemiology and Control)
In impoverished nations, intestinal protozoan infections (IPIs) are a leading cause of diarrhea in children. However, in the majority of afflicted nations, including Ethiopia, the role played by each intestinal protozoa species in causing diarrhea and the risk factors linked with it are not adequately addressed. This would support focused intervention efforts. The prevalence of IPIs and related variables were evaluated between April and May 2023 among 380 under-five children in Borena district of Amhara region, central Ethiopia, by an institution-based cross-sectional survey. Systematic random sampling was used to select study participants. The study included a structured questionnaire to gather data regarding sociodemographic characteristics and perceived risk factors for IPIs. Using saline and iodine wet mounts as well as Richie's modified formol-ethyl acetate concentration technique, stool samples were collected and analyzed under a microscope. SPSS was used to enter and evaluate the data. At a 95 % confidence level, bivariate and multivariate logistic regressions were used to determine the factors linked to intestinal protozoa infection. Among 380 participants, 136 (35.8 %) were tested positive for one or more intestinal parasite species at least by one of the diagnostic methods. 118 (31.1 %; 95 % CI: 26.6–36.1) children were infected by intestinal protozoans.The parasites detected were: G. lamblia 71 (18.7 %) and E. histolytica/disar 54 (14.2 %), E. vermicularis 3 (0.8 %), A. lumbricoides 2 (0.5 %), H. nana 2 (0.5 %) and T. trichiura 1 (0.3 %). Seven (1.8 %) participants were infected by both protozoan species. Children whose mothers/guardians did not attend formal education were at higher risk of IPI (adjusted odds ratio (AOR) = 2.801; 95 %CI: 1.666–4.711, p < 0.001) than children from literate mothers/guardians. Absence of functional toiltet in the household (AOR = 1.952; 95 %CI: 1.195–3.187, p = 0.008), hand washing with water alone, rather than with soap/ash (AOR = 3.052; 95 %CI: 1.203–7.746, p = 0.019) and having frequent contact with animals (AOR = 2.103; 95 %CI: 1.238–3.574, p = 0.006) were associated with IPIs. These findings revealed that Giardia lamblia and Entamoeba histolytica are public health problems causing diarrhea among under-five children in the study area, and their transmission is associated with the illiteracy of mothers/guardians, the absence of functional toilets, not using soap/ash during hand washing, and frequent contact with domestic animals. Therefore, when diagnosing, treating, and educating patients about diarrhea, healthcare professionals should take these protozoans into account.